The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ijc.31609
|View full text |Cite
|
Sign up to set email alerts
|

SOX2‐mediated upregulation of CD24 promotes adaptive resistance toward targeted therapy in melanoma

Abstract: Melanoma is often characterized by a constitutively active RAS-RAF-MEK-ERK pathway. For targeted therapy, BRAF inhibitors are available that are powerful in the beginning but resistance occurs rather fast. A better understanding of the mechanisms of resistance is urgently needed to increase the success of the treatment. Here, we observed that SOX2 and CD24 are upregulated upon BRAF inhibitor treatment. A similar upregulation was seen in targeted therapy-resistant, melanoma-derived induced pluripotent cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 49 publications
(124 reference statements)
5
47
0
Order By: Relevance
“…In agreement with earlier results, treatment with mibefradil on human adaptive cells suppressed expression of differentiation markers associated with adaptive resistance 28,29 in both parental and adaptive cells ( Supplementary Fig. S9a, b, c).…”
Section: Inhibition Of T-type Calcium Channels Increases Drug-sensitisupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with earlier results, treatment with mibefradil on human adaptive cells suppressed expression of differentiation markers associated with adaptive resistance 28,29 in both parental and adaptive cells ( Supplementary Fig. S9a, b, c).…”
Section: Inhibition Of T-type Calcium Channels Increases Drug-sensitisupporting
confidence: 92%
“…Reduction of SOX2 expression was also confirmed with CACNA1H knockdown in human melanoma cells. 28 Together, these results conclude that the inhibition of T-type calcium channels induces differentiation in MAPKi-adaptive cells, suggesting the participation of calcium signalling in the stemness maintenance and drug adaptation in melanoma cells.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, enhanced activity of STAT3 followed by increased expression of SOX2, which were observed only in 28_PLXR cells could be also considered as the mechanism supporting cell survival. It has been demonstrated that SOX2 as a part of STAT3-SOX2-CD24 axis rescued melanoma cells against acute exposure to vemurafenib [69]. SOX2 was shown to contribute to the stable reprogramming of melanoma cells to their undifferentiated counterparts that were resistant to inhibitors of the MAPK signaling pathway independently of which of oncogenic mutations in the MAPK pathway (BRAF or NRAS) was present [70], and SOX2-positive cells were reported in melanoma cell populations exerting a drug-tolerant state to combined dabrafenib and trametinib treatment [71].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, STAT3 was demonstrated to be upregulated in cancer stem cells [3] as well as together with SOX2 in clustered circulating tumor cells, which have a high metastatic potential [4]. In our publication [5] we could demonstrate that the initial STAT3 activation induced by BRAF inhibitor treatment resulted in an increased expression of SOX2 and CD24 which were both associated to an increased resistance since overexpression of either SOX2 or CD24 resulted in a significantly higher tolerance against BRAF inhibitors. In contrast, the knock down of both molecules rendered cells more sensitive towards the treatment.SOX2 was demonstrated before to be a cancer stem cell marker and its expression is increased in melanospheres which showed a higher resistance towards the BRAF inhibitor vemurafenib [6,7].…”
mentioning
confidence: 61%